Konsep Mītsāqan Ghalīẓan dan ‘āsyirūhunna bil-ma‘rūf Dalam QS. an-Nisa: 19-21 terhadap Problematika “Marriage Is Scary” - Shafwatul Insani; Rindiani Putri (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
The phenomenon of “marriage is scary” represents the fear of the younger generation, especially Gen Z, towards the institution of marriage. This fear is triggered by various factors such as patriarchal culture, domestic conflict, the influence of social media, and shifts in social values. This study aims to respond to this phenomenon by reviewing the concept of household resilience from the perspective of the Qur'an. This study uses a qualitative method with a library research approach, which traces the verses of the Qur'an regarding the values ​​of marriage. The main findings show that the Qur'an offers the principle of household resilience through two central concepts, namely mītsāqan ghalīẓan (a solid agreement) and 'āsyirūhunna bil ma‘rūf (getting along with one's wife well). These two principles emphasize the importance of spiritual commitment, ethics of mu‘āsyarah, and reciprocal responsibility in forming a sakinah, mawaddah, wa raḥmah family. Thus, the Qur'an provides conceptual and practical solutions to address the concerns of the younger generation regarding marriage, and offers a solid framework of values ​​in building harmonious and just household relationships.